Super aggregators and the media supply chain. (August 2021) - O'Regan, Tom; Balnaves, Mark
Search engines and social media came into their own from 2006. Indeed, when regulators in the United States crafted Section 230 in the 1990s to give immunity to web publishers from third-party content, they did not know that search services would become hypergiant advertising and news vehicles. In this article, the authors argue that the sudden upending of established practices in the media industries has far-reaching consequences for how audiences are represented for businesses and the public.